Developing Students’ Worksheet of Cuboid and Cube Volume with Realistic Mathematics Education (RME) - Oktavia, Siwi Putri; Shodikin, Ali; Ekawati, Rooselyna (Journal of the Indonesian Mathematics Education Society, 2025)
The aim of this study is to develop a Student Worksheet for students of 8th grade SMP of cube and cuboid volume material based on Realistic Mathematics Education (RME) which have valid and practical criteria. It was development research, adapted from the 4D development model. Validation was carried out by material, media, and learning experts. The Student Worksheet developed was tested in a small group test with the subjects of 6 students. The results showed the RME-based Student Worksheet is valid by evidence that an average total score of 3.24 was obtained with a percentage of 80.92%. The assessment by the students was performed in a small group test to test the practicality. From a small group test, an average total score of 3.44 was obtained with a percentage of 86%. Therefore, this RME-based Student Worksheet is valid and practical.